Horizontal and Vertical Distance Perception in Altered Gravity - Clément, Gilles; Bukley, Angie; Loureiro, Nuno; Lindblad, Louise; Sousa, Duarte; Zandvilet, André (Scientific reports, 2020)
The perception of the horizontal and vertical distances of a visual target to an observer was investigated in parabolic flight during alternating short periods of normal gravity (1 g). microgravity (0 g), and hypergravity (1.8 g). The methods used for obtaining absolute judgments of egocentric distance included verbal reports and visually directed motion toward a memorized visual target by pulling on a rope with the arms (blind pulling). The results showed that, for all gravity levels, the verbal reports of distance judgments were accurate for targets located between 0.6 and 6.0 m. During blind pulling, subjects underestimated horizontal distances as distances increased, and this underestimation decreased in 0 g. Vertical distances for up targets were overestimated and vertical distances for down targets were underestimated in both 1 g and 1.8 g. This vertical asymmetry was absent in 0 g. The results of the present study confirm that blind pulling and verbal reports are independently influenced by gravity. The changes in distance judgments during blind pulling in 0 g compared to 1 g support the view that, during an action-based task, subjects base their perception of distance on the estimated motor effort of navigating to the perceived object.